Robust segmentation of brain structures in MRI - Murgasova, M.; Rueckert, D.; Edwards, D.; Hajnal, J. (2009 IEEE International Symposium on Biomedical Imaging: From Nano to Macro, 2009)
A novel method for the segmentation of brain structures combining registration-based and EM-based approaches is proposed. To address the issue of intensity variation within brain structures, we propose a method for creating spatial prior corresponding very well with the new subject anatomy, referred to as subject-specific atlas. The subject-specific atlas is created using multiple non-rigid registrations with the new subject, and therefore a robust non-rigid alignment of the prior with the image is achieved. The final EM segmentation step ensures a good quality classification of the complicated cortical structures based on intensity. The evaluation of the proposed method shows consistent results superior to both, registration-based and EM-based approaches.